Pleistocene climatic oscillations rather than recent human disturbance influence genetic diversity in one of the world's highest treeline species. Issue 10 (5th October 2015) - Peng, Yanling; Lachmuth, Susanne; Gallegos, Silvia C.; Kessler, Michael; Ramsay, Paul M.; Renison, Daniel; Suarez, Ricardo; Hensen, Isabell
Abstract : PREMISE OF THE STUDY: Biological responses to climatic change usually leave imprints on the genetic diversity and structure of plants. Information on the current genetic diversity and structure of dominant tree species has facilitated our general understanding of phylogeographical patterns. METHODS: Using amplified fragment length polymorphism (AFLPs), we compared genetic diversity and structure of 384 adults of P. tarapacana with those of 384 seedlings across 32 forest sites spanning a latitudinal gradient of 600 km occurring between 4100 m and 5000 m a.s.l. in Polylepis tarapacana (Rosaceae), one of the world's highest treeline species endemic to the central Andes. KEY RESULTS: Moderate to high levels of genetic diversity and low genetic differentiation were detected in both adults and seedlings, with levels of genetic diversity and differentiation being almost identical. Four slightly genetically divergent clusters were identified that accorded to differing geographical regions. Genetic diversity decreased from south to north and with increasing precipitation for adults and seedlings, but there was no relationship to elevation. CONCLUSIONS: Our study shows that, unlike the case for other Andean treeline species, recent human activities have not affected the genetic structure of P. tarapacana, possibly because its inhospitable habitat is unsuitable for agriculture. The current genetic pattern of P. tarapacana points to a historically more widespread distribution at lower altitudes, which allowed considerable gene flow possibly during the glacial periods of the Pleistocene epoch, and also suggests that the northern Argentinean Andes may have served as a refugium for historical populations.